High precision calculation of multipolar dynamic polarizabilities and two- and three-body dispersion coefficients of atomic hydrogen - Cebim, M. A. [UNESP]; Masili, Mauro; De Groote, J. J. (Springer Wien, 2009)
In this paper we investigate a variationally stable procedure for multipolar dynamic polarizabilities calculation as well as the two- and three-body van der Waals coefficients of the hydrogen atom. This approach provides precise, fast convergent values for real and imaginary frequency-dependent 2 (L) -pole dynamic polarizabilities. Highly accurate two- and three-body van der Waals dispersion coefficients are calculated from dynamic polarizabilities at imaginary photon frequencies. The present approach is also precise for higher interaction orders. The results are compared with previous calculations found in the literature.